2022
DOI: 10.1088/2399-6528/ac72f8
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and optimal protocols of multidimensional quadratic Brownian systems

Abstract: We characterize finite-time thermodynamic processes of multidimensional quadratic overdamped systems. Analytic expressions are provided for heat, work, and dissipation for any evolution of the system covariance matrix. The Bures-Wasserstein metric between covariance matrices naturally emerges as the local quantifier of dissipation. General principles of how to apply these geometric tools to identify optimal protocols are discussed. Focusing on the relevant slow-driving limit, we show how these results can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…The movement of fungicide smoke also obeys the Brownian movement and kinetic theory of gases. This theory indicated that particles move faster at higher temperatures and thus the uniformity of smoke generated by 300 °C is worse than 600 °C 23,24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of fungicide smoke also obeys the Brownian movement and kinetic theory of gases. This theory indicated that particles move faster at higher temperatures and thus the uniformity of smoke generated by 300 °C is worse than 600 °C 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…This theory indicated that particles move faster at higher temperatures and thus the uniformity of smoke generated by 300 °C is worse than 600 °C. 23,24 When the substance was heated to smoke, it would float in the air for a long time as the smoke particles had large kinetic energy. 25 These particles also had the same charge and they were mutually exclusive to maintain athletic performance and floatation.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of introducing f * (t) is to explicitly include the initial and final jumps. According to equation (38), one can easily check that f * (0) = 0 and f * (τ) = 1. As we show next, this is necessary to give the correct physical meaning to the excess power calculations.…”
Section: Excess Powermentioning
confidence: 99%
“…Although restricted to limited non-equilibrium regimes, these formulations might provide a better physical intuition about the optimal processes. Among these perturbative formulations, the so-called geometric one has attracted considerable attention in the last decade [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. It has been applied to different non-equilibrium situations in biophysics [31,33,36], magnetic systems [29,30,35], heat engines [34], and solid-state physics [39], in addition to having been extended to quantum systems [27,32].…”
Section: Introductionmentioning
confidence: 99%
“…For either full or parametric control, the exact minimum-dissipation protocol is known if the probability distribution is Gaussian [35][36][37]. These exact solutions provide a glimpse into the properties of optimal control processes.…”
Section: Introductionmentioning
confidence: 99%